2021
DOI: 10.3390/plants10102113
|View full text |Cite
|
Sign up to set email alerts
|

How Effective Are the Protected Areas of the Natura 2000 Network in Halting Biological Invasions? A Case Study in Greece

Abstract: Invasive alien plant species represent an important threat to various protected areas of the world, and this threat expected to be further enhanced due to climate change. This is also the case for the most important network of protected areas in Europe, the Natura 2000 network. In the current study we evaluated the distribution pattern of alien plant taxa across selected continental and insular Natura 2000 sites in Greece and their potential spread 15 years since first being recorded in the field. A total of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…This indicates that biological invasions are already affecting not only ecological corridors but also core areas with high ecological sensitivity in Hungary [16], similar to other European countries [2,3,[42][43][44]. Therefore, targeted management practices (e.g., mowing, grazing, and mechanical control) are required to suppress the populations of invasive species and to maintain ecosystem services within protected areas [45][46][47].…”
Section: Discussionmentioning
confidence: 91%
“…This indicates that biological invasions are already affecting not only ecological corridors but also core areas with high ecological sensitivity in Hungary [16], similar to other European countries [2,3,[42][43][44]. Therefore, targeted management practices (e.g., mowing, grazing, and mechanical control) are required to suppress the populations of invasive species and to maintain ecosystem services within protected areas [45][46][47].…”
Section: Discussionmentioning
confidence: 91%
“…Transport also influences biodiversity through the transfer of alien species. For example, alien species are assumed to have arrived as stowaways (Lambdon et al, 2008) and highly disturbed habitats like grasslands with close proximity to transportation networks experience more propagule pressure (Christopoulou et al, 2021). The negative influence of biodiversity on transport include damage from wild boars that cause local erosion in areas connected to roads (Mauri et al, 2019) and the protection of natural areas preventing further development of transport infrastructure .…”
Section: Biodiversity-food-transport Nexusmentioning
confidence: 99%
“…As Vicente et al [170] have shown, invasive populations of perennial alien plants pose a major threat to the establishment and maintenance of functional ecological linkages between areas of high conservation value. Species with such high dispersal potential and a competitive nature may exploit the establishment of corridors and use them as pathways for further dispersal into areas of high conservation value [52,171,172]. In such cases, the design of ecological corridors should be redesigned [172].…”
Section: Orchards Greecementioning
confidence: 99%